Unveiling the RNA virosphere associated with marine microorganisms. (6th September 2018) - Urayama, Syun‐ichi; Takaki, Yoshihiro; Nishi, Shinro; Yoshida‐Takashima, Yukari; Deguchi, Shigeru; Takai, Ken; Nunoura, Takuro
Abstract: The study of extracellular DNA viral particles in the ocean is currently one of the most advanced fields of research in viral metagenomic analysis. However, even though the intracellular viruses of marine microorganisms might be the major source of extracellular virus particles in the ocean, the diversity of these intracellular viruses is not well understood. Here, our newly developed method, referred to herein as fragmented and primer ligated dsRNA sequencing (flds ) version 2, identified considerable genetic diversity of marine RNA viruses in cell fractions obtained from surface seawater. The RNA virus community appears to cover genome sequences related to more than half of the established positive‐sense ssRNA and dsRNA virus families, in addition to a number of unidentified viral lineages, and such diversity had not been previously observed in floating viral particles. In this study, more dsRNA viral contigs were detected in host cells than in extracellular viral particles. This illustrates the magnitude of the previously unknown marine RNA virus population in cell fractions, which has only been partially assessed by cellular metatranscriptomics and not by contemporary viral metagenomic studies. These results reveal the importance of studying cell fractions to illuminate the full spectrum of viral diversity on Earth.